MANAJEMEN RISIKO BANK ISLAM (PENANGANAN PEMBIAYAAN BERMASALAH DALAM PRODUK PEMBIAYAAN PADA PT. BANK MUAMALAT CABANG PEMBANTU PANYABUNGAN) - Jureid Jureid (Journal Analytica Islamica, 2016)
Risk management is an important effort that must be done by each company, including Islamic banking, as an effort to minimize losses due to the risk. Bank Muamalat of Panyabungan manage the risk by applying the process of Financing Risk Assessment (FRA) on some aspects and then continued with intensive billing, give warning, applying revitalization process by rescheduling, reconditioning, and restructuring, completion with guarantee, as well as take the path of litigation and at the same time monitoring and controlling. Strategic SWOT that can apply is by Strengthen Regulation of internal bank, Recruiting competent employees, , revitalizing maximumly and rigorously, developing a reliable risk management system, specializing MSME financing, Doing emotional service improving the ability of FRM, implementing office chanelling, strengthen the treaty clause. In the application of risk management at Bank Muamalat Branch Panyabungan, fairness and the principle of legal certainty has been applied and walk in unison and not against each other.